2011
DOI: 10.1890/es10-00142.1
|View full text |Cite
|
Sign up to set email alerts
|

Do rebuttals affect future science?

Abstract: Abstract. In theory, rebuttals play a vital role in the progression of science, pointing out flaws in published articles, and ensuring that science self-corrects. However, the effect of rebuttals has not been tested in practice. We examined seven high-profile original articles and their rebuttals, finding that original articles were cited 17 times more than rebuttals, and that annual citation numbers were unaffected by rebuttals. When citations did not mention rebuttals, 95% accepted the thesis of the original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
1
26
0
1
Order By: Relevance
“…Furthermore, humans have overexploited >90% of the economically important species of the coastal seas (Lotze et al 2006), and in Europe, there are concerns regarding the long-term sustainability of local fish stocks (Froese & Proelß 2010;Thurstan et al 2010;Gu enette & Gascuel 2012). However, there is strong disagreement amongst scientists as to the impact of overfishing (for a synthesis, see Banobi et al 2011). Some of the differences derive from abundance estimates that are based on catch data from commercial fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, humans have overexploited >90% of the economically important species of the coastal seas (Lotze et al 2006), and in Europe, there are concerns regarding the long-term sustainability of local fish stocks (Froese & Proelß 2010;Thurstan et al 2010;Gu enette & Gascuel 2012). However, there is strong disagreement amongst scientists as to the impact of overfishing (for a synthesis, see Banobi et al 2011). Some of the differences derive from abundance estimates that are based on catch data from commercial fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the impact of retracted articles in the biomedical literature from 1966 to 1997 found that even after publication of the retraction most of these articles continue to be cited as valid work with no mention of the retraction [92], with most citations implicitly or explicitly positive [98] even up to 24 years post retraction [99]. A more recent publication also found that a retraction did not affect the paper's citations rate within 12 months of retraction [100] and an investigation of the effect of rebuttals on seven high-profile original articles found that original articles were cited much more frequently than the rebuttals, with no reduced effect on annual citation numbers [101]. In contrast, other reports found that retraction significantly reduced subsequent citation [102], [103] and that this reduction extends to the authors’ other published work [104].…”
Section: Hype and Retractionsmentioning
confidence: 99%
“…Banobi et al (2011) reported that high-profile environmentalist articles were cited 17 times more frequently than their peer-reviewed critiques, even when the originals were challenged by independent scientists on several different occasions. Furthermore, articles that did not cite the critiques almost always accepted the results of the original reports without adequate evaluation of the claims.…”
Section: Media Coverage and Public Perceptionmentioning
confidence: 99%